Prototype of Integrated Power Meter & Automatic Power Factor Controller for Optimizing Electric Power Quality - Bagus Pramono (Fakultas Teknik Universitas PGRI Banyuwangi, 2024)
The increasing focus on energy efficiency highlights the need for improving electrical systems, particularly regarding power factor optimization. This study develops a prototype Integrated Power Meter & Automatic Power Factor Controller using an Arduino Uno microcontroller. The system measures electrical parameters, including reactive power, voltage, and current, in real-time. It automatically adjusts power factor by activating capacitors based on system requirements. Testing reveals significant improvements, with power factor enhancement by over 20% and reduced reactive power by up to 80%. The prototype demonstrates potential for application in industrial settings, offering an effective solution for energy management.